Digital leadership and exploratory innovation: From the dual perspectives of strategic orientation and organizational culture - Wang, Tiandong; Lin, Xiaoyue; Sheng, Fan (Frontiers in Psychology, 2022)
The literature on leadership is increasingly supporting the power of digital leadership in promoting corporate innovation. In spite of this, digital leadership is a noticeable omission from the literature. As such, in this study, we developed a model based on a resource-based view and social information processing theory to examine the roles of digital entrepreneurial orientation and digital organizational culture in the relationship between digital leadership and exploratory innovation. We examined the moderating role of big data analytics capabilities according to a resource-based view and dynamic capability theory. Using a time-lagged survey data of 401 followers and 88 leaders, the results show that (a) digital leadership has a positive impact on exploratory innovation; (b) digital entrepreneurial orientation and digital organizational culture mediate the positive relationship between digital leadership and exploratory innovation; and (c) and mediating effect is positive moderated by big data analytics capabilities. Thus, in this study we are not only responding to the call to strengthen digitalization research in organizations but also further deepening our understanding of the path from digital leadership to exploratory innovation. These findings have theoretical implications for the literature on leadership and managerial implications for practitioners.